Analisis Kemajuan Tambang Bulanan Pada Aktivitas Overburden Removal Di PT “X” Kabupaten Muara Enim Provinsi Sumatera Selatan: Analysis Of Monthly Mine Progress on Overburden Removal Activity In PT “X” Muara Enim Regency, South Sumatera Province - Siti Hardianti; Rinda Pasari; Maryana (MINERAL, 2026)
Mining progress analysis was conducted by comparing the monthly plan with the results of the end-of-month survey. This study used a quantitative method, because it uses numbers in its analysis. The purpose of this study was to determine mining progress based on area, depth, and volume, compare survey progress, and analyze factors that influence the achievement of overburden production. Based on the comparison of the monthly plan and topography progress, the results of mining progress were obtained based on 100% area. Based on depth, different percentage achievements were obtained at each elevation ranging from 0% to 100%. And the achievement of mining progress based on volume was 52.20%. Factors that influenced the failure to achieve overburden production, both in terms of depth and volume, included: the use of equipment that did not comply with the plan so that the overburden fleet was not realized from the plan, high rainfall and reduced operating hours due to the month of Ramadan. Efforts that can be made to improve the achievement of overburden production include ensuring the suitability of the number and capacity of equipment according to the planned fleet, reducing bottlenecks, conducting routine equipment maintenance, and optimizing the drainage system so that mining activities continue to run during high rainfall.